Republicanism within IR: A History of Liberty and Empire. (September 2019) - Blachford, Kevin
The republican tradition has long been influential within political theory, but has been less acknowledged within the discipline of International Relations (IR). Republican theorists and republican ideas of political liberty underlie many normative claims made by both liberal and realist schools of thought. The following examination of republicanism takes an interdisciplinary approach to argue the relevance of republicanism for IR theory. When republicanism is recognised within IR, it is often through a triumphalist reading of the early American republic and its founding. This article opens new ground by presenting a more critical account of republicanism. It does so by focusing on the connections between republican liberty and the history of republics to dominate those outside the polis. El republicanismo en el ámbito de las relaciones internacionales: Una historia de libertad e imperio